CULT OF SNAKES IN BELIEFS OF PEOPLES IN EURASIA - Матюхіна, О. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article represents the definite mythological parallels dealing with the link between the cult of snakes and the cult of Great Goodness in the system of beliefs of peoples of Eurasia.